An Analytical Approach for Estimating Optimal Multi‐Layer Network Cost, Exploiting the Flexible‐Grid Optical Technology. (December 2013) - Paparella, Andrea; Gemelli, Riccardo; Leven, Andreas; Varma, Eve L.
Abstract In this paper we provide analytical insights for dimensioning a multi‐layer network and in particular the virtual optical transport network topology exported to the packet client layer according to cost and power consumption. A new approach is described, approximating optimum routing, that can be effectively used to provide an estimation of network cost and reference architectures in network implementations. Results using this estimation approach are compared with those obtained using other estimation approaches regarding bandwidth allocation and network costs. We found that the approximated routing calculations, applied on a virtual network topology, do not significantly penalize the accuracy of the results. This approach can be extended to analyze the impact of new a optical networking technique, flexible‐grid wavelength division multiplexing (WDM), providing some insights regarding scenarios in which migration from fixed‐grid WDM systems to flexible‐grid WDM systems would be advantageous in terms of capital cost and power consumption. © 2013 Alcatel‐Lucent.